The Efficacy and Safety of <2 cm Micro-Keyhole Microvascular Decompression for Hemifacial Spasm - Huang, Jiashang; Zhan, Yan; Li, Yi; Jiang, Li; Wang, Kuan; Wu, Zhimin; Xie, Yanfeng; Shi, Quanhong (Frontiers in Surgery, 2021)
Objective: Our study was designed to describe and evaluate the efficacy and safety of keyhole microvascular decompression to manage patients with hemifacial spasm (HFS). Methods: A total of 148 patients with hemifacial spasm diagnosed in the First Affiliated Hospital of Chongqing Medical University from January 1, 2019 to July 1, 2020 who underwent microvascular decompression in the neurosurgery department of our hospital were collected. Surgery was performed by a retrosigmoid keyhole approach. The size of bone hole was about 15mm*18mm. The efficacy and safety of keyhole microvascular decompression were evaluated by statistical analysis of the efficacy of Microvascular Decompression surgery and the incidence of postoperative complications. Results: The effect of Microvascular Decompression was satisfying (cure or partial remission) in 97.2% (n = 144). The failure and recurrence rates were 2.7% (n =4) and 0.6% (n = 1), respectively. Among them, immediate facial palsy, delayed facial palsy, hearing loss, and cerebrospinal fluid leakage were found in 0.6% (n = 1), 8.1%(n=12),4.7% (n = 7), and 1.3% (n = 2). Only one patient developed cerebellar infarction, which was complicated by moyamoya disease. Keyhole microvascular decompression in the treatment of hemifacial spasm can achieve a high remission rate and reduce the incidence of surgical complications. Conclusion: Keyhole microvascular decompression is a safe and effective minimally invasive treatment for HFS. This technique does not increase the incidence of cranial nerve injury, meanwhile it reduces the incidence of cerebrospinal fluid leakage and hearing loss.